Determinação de hidrocarbonetos policíclicos aromáticos em solos por extração em disco rotatório, espectrofluorimetria e calibração de ordem superior - Freitas, Anne Caroline Pinheiro de (2021)
Polycyclic aromatic hydrocarbons (PAH) are organic micropollutants substances that are persistent in the environment and have a high mutagenic and carcinogenic capacity. Environmental monitoring of PAH levels is necessary because of such risks. In the analysis and determination of PAH, the most used technique is chromatography. However, it has high financial and temporal costs. Thus, membrane filtering spectrofluorimetry and second-order calibration appear as an alternative for the determination of these components. In this work, we used pre-concentration in nylon membrane by rotating-disk to determine four PAH: anthracene, phenanthrene, benzo[a]pyrene, and chrysene in eight types of soils from extraction with acetonitrile/H2O (1:1, v/v), followed by concentration on nylon membrane in a rotating-disk. PARAFAC was used as a higher-order method for the deconvolution of the profiles and prediction of the PAH in the samples. Recoveries remained in the 83-116% range and, the Percentual Relative Error of Prediction the percent forecast error between 5-6.2%. Thus, the analytes were predicted in the presence of interferents, which brings the possibility of extending the determination to others complex and real matrices.